Otonan Alit Media Training to Boost the Self-Confidence of Hindu Women in Banjar Dharma Praja Giri Menang, West Lombok Regency - Saridewi, Desak Putu; Wiasti, Ni Komang; Ratnadewi, Ni Luh Sinar Ayu; Wiranata, I Made Pandya; Rencani, Ni Ketut; Wijana, I Nyoman; Zaenab, Siti; Dikta, Putu Gede Asnawa (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2026)
The Pawotonan ritual is an important tradition for celebrating birthdays according to the Wuku calendar. However, over time, the philosophical values and symbolic meanings of Otonan, particularly Otonan Alit, have changed. The emergence of Gen Z birthday traditions has become dominant, thus obscuring the Otonan tradition. Ironically, Hindu women have slowly followed modern trends and nearly forgotten the tradition. Women in Bali are expected to have a broad understanding and skill set related to religious rituals, offerings, customs, and culture. In this context, preserving and strengthening cultural values through traditional media, such as Otonan Alit, is important and relevant. This study employs a qualitative approach with community service activities, including training on the production of Otonan offerings. This training will take place in the village of Dharma Praja, Giri Menang, Lombok Barat, on July 13, 2025. The training uses an observational approach based on participants' social conditions and abilities. The discussion is conducted in a humanistic manner to discuss participants' abilities to perform the Otonan ritual with their respective traditions. The documentation method was used to supplement the data obtained during the activity. The study focuses on creating banten otonan according to Hindu religious texts. The subjects/participants are the WHDI, Dharmika, and Srathi of Lombok Barat. The results of the training showed that the Otonan Alit medium can be an effective educational and reflective tool for fostering self-confidence, pride in identity, and awareness of the role of women in maintaining family and community harmony.